Innovative Finance: Learning on CGIAR’s Ways of Working - CGIAR Independent Advisory and Evaluation Service (CGIAR Independent Advisory and Evaluation Service, 2025)
The CGIAR 2030 Research and Innovation Strategy sets the stage for doing business differently to ensure that research provides real solutions for development. To support these changes, CGIAR is committed to following seven new implementation approaches, or Ways of Working (WoWs). This brief summarizes key findings from an evaluative learning report on one of CGIAR’s Way of Working on innovative finance as a mechanism to support delivery of its research and innovation agenda.